Cryoballoon ablation for persistent atrial fibrillation in patients without left atrial fibrosis. (11th April 2019) - Gramlich, Michael; Maleck, Carole; Marquardt, Jonathan; Duckheim, Martin; Stimpfle, Fabian; Heinzmann, David; Scheckenbach, Christian; Gawaz, Meinrad; Schreieck, Jürgen; Seizer, Peter
Abstract: Introduction: The role of cryoballoon (CB) pulmonary vein isolation (PVI) for patients with persistent atrial fibrillation (AF) is controversial, since long‐term success can be poor. We performed left atrial voltage mapping before CB PVI and determined AF‐free survival depending on the extent of low‐voltage areas (LVAs). Methods and Results: We consecutively enrolled 60 patients with persistent AF (average age, 60.6 ± 12.9 years; CHA2 DS2 VASc score, 2.3 ± 1.6; and left atrial size 46.0 ± 5.2 mm) who were planned for CB PVI. Before ablation, we performed left atrial voltage mapping (Abbott EnSite Precision or Velocity). LVAs were defined if local bipolar signal amplitudes were less than 0.5 mV during sinus rhythm. Thirty‐seven patients did not show significant LVAs (<10%), while 12 patients had LVAs between 10% and 30% and 11 patients showed substantial LVAs greater than 30% of the left atrial area. CB PVI could be successfully performed in all patients. A 7‐day holter monitoring was obtained 3, 6, and 12 months after ablation. After a 12‐month follow‐up time, 83.8% of patients without LVAs (<10%) were free of atrial fibrillation, while 50.0% of patients with 10% to 30% LVAs and 9.1% of patients with LVAs more than 30% had stable sinus rhythm. The degree of atrial fibrosis correlated with the risk of AF recurrence. Conclusion: In patients with persistent AF undergoing CB PVI, the extent of left atrial LVAs predicts an AF‐free survival. CB PVI seems to be a highly effective treatment for patients with persistent AF without atrial fibrosis.